Análise dos elementos críticos para gerenciamento da segurança operacional (SGSO) em uma empresa multinacional de produção e manutenção de motores aeronáuticos - Pereira, José Cristiano (2012)
Hazards and risks and many critical elements are present in the thousands of activities required to manufacture or overhaul an aircraft engine. The available literature about risks applicable to this industry is very limited. This dissertation aims to analyze and discuss the risk factors and critical elements for developing an operational safety management system in an aircraft engines production and overhaul company. As a methodological approach a predominantly qualitative, bibliographical and empirical study was adopted, supported by a field survey conducted in a multinational industry of production and overhaul of aircraft engines. The main result is the definition and analysis of the risk factors and critical elements for developing the proposed model